SPATIOTEMPORAL MONITORING OF GROUND COVER CHANGES (NDVI AND LST) IN THE BOZSHAKOL MINE KAZAKHSTAN USING INTEGRATED REMOTE SENSING AND GEOSPATIAL APPROACH - Shah, Zahid (Nazarbayev University School of Mining and Geosciences, 2025)
Mining activities have significant negative environmental impacts, particularly in terms of land cover degradation and temperature changes. This study assesses these environmental impacts associated with Bozshakol open pit mine in Northeastern part of Kazakhstan through remote sensing geospatial approach. The methodology incorporates the use of Normalized Difference Vegetation Index (NDVI), and Land Surface Temperature (LST) data extracted from Landsat 8/9 database to assess land cover changes and surface temperature variations from 2013 to 2023. Climatic factors, that include precipitation, air temperature, and relative humidity, are also evaluated and correlated to differentiate between mining-induced changes and natural climate variability. The findings show significant decrease in NDVI values post-2016, correlating with increased mining activities. The vegetation loss, which is lower NDVI values, has also resulted LST rising significantly in different section of study area. In terms of climate data, the result shows that higher precipitation years (2016 and 2018) has led to temporarily stabilization of NDVI values, however, overall vegetation decline continued, suggesting that land degradation from mining outweighed the benefits of rainfall. Likewise, the decreasing relative humidity trend and increasing air temperature trend correlate with the land surface warming. The spatiotemporal analysis of mine section of the study area showed an increased pit boundary, waste dump and tailing area between the years 2017 and 2024 which is the period of post-mining. Mine tailings increased from 7 km² to more than 14 km² and waste dumps from 1 km² to 4.5 km². This growth is directly linked to vegetation loss, increased land surface temperature, and landcover changes. The findings from this study highlights the need for sustainable mining practices, land rehabilitation, vegetation restoration, and improved waste management associated with Bozshakol mine. Stricter environmental regulations and climate adaptation strategies must be integrated to mitigate long-term environmental damage. Environmental monitoring and responsible mining operations are essential to balancing resource extraction with environment preservation.
Keywords: Type of access: Embargo